2016
DOI: 10.1080/1533256x.2016.1146612
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Interpersonal Violence Victimization and Smoking Behavior Across Time and by Gender

Abstract: The current study examined relationships between interpersonal violence victimization and smoking from childhood to adulthood. Data were from a community-based longitudinal study (N = 808) spanning ages 10 - 33. Cross-lag path analysis was used to model concurrent, directional, and reciprocal effects. Results indicate that childhood physical abuse predicted smoking and partner violence in young adulthood; partner violence and smoking were reciprocally related in the transition from young-adulthood to adulthood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 103 publications
0
4
0
2
Order By: Relevance
“…The resultant tailored intervention is woman centered, harm reducing, trauma informed, and equitable. Harm-reduction and woman-centered approaches are consistent with the 2014 guidance, and we deemed that a trauma-informed approach was important because of the strong correlation between smoking and the experience of trauma (Holl et al, 2017;Kristman-Valente et al, 2016;Ullman et al, 2013). Traumainformed approaches to smoking are also important given the perception by women that smoking reduces stress.…”
Section: Development Of the Interventionmentioning
confidence: 96%
See 1 more Smart Citation
“…The resultant tailored intervention is woman centered, harm reducing, trauma informed, and equitable. Harm-reduction and woman-centered approaches are consistent with the 2014 guidance, and we deemed that a trauma-informed approach was important because of the strong correlation between smoking and the experience of trauma (Holl et al, 2017;Kristman-Valente et al, 2016;Ullman et al, 2013). Traumainformed approaches to smoking are also important given the perception by women that smoking reduces stress.…”
Section: Development Of the Interventionmentioning
confidence: 96%
“…Trauma-informed approaches to tobacco reduction and cessation reflect emerging evidence on the links between trauma, violence, and tobacco use. The prevalence of smoking is great among women who experienced childhood abuse and intimate partner violence (Kristman-Valente et al, 2016) and sexual assault and rape (Amstadter et al, 2009). Approaches that are confrontational, authoritative, or directive can feel unsafe or retraumatizing for women with histories of trauma and should be avoided (Hemsing, Greaves, & Poole, 2015).…”
Section: Trauma-informed Approachmentioning
confidence: 99%
“…Findings concerning sex differences in the linkages between a history of childhood abuse and adult health are not consistent. While in some investigations sex has not been identified as a significant moderating factor in the relationship between abusive childhood experiences and adult physical and mental health [41,42,43], other studies have showed that sex interacts with the type of child abuse experienced to determine specific negative effects on adult physical and mental health [15,44,45,46,47,48]. Furthermore, the studies indicating differential effects of childhood abuse on the health of men and women show divergent results regarding the sex of those adults more at risk of developing physical and/or psychological symptoms following childhood abuse.…”
Section: Introductionmentioning
confidence: 99%
“…Dentro da investigação de uma rota predominante, há a possibilidade de configurações de padrões de rotas homogêneos, que ocorre quando todas as regressões cruzadas possíveis de uma rota obtém significância estatística. A figura 3, a seguir, inspirada em Kristman-Valente et al (2016), retrata os três principais painéis de rotas homogêneas: Figura 3: os três principais painéis de rotas homogêneas para o modelo CLPM Nota: Painel A: preocupações como variável preditora dos sintomas depressivos; Painel B: sintomas depressivos como variável preditora das preocupações; Painel C: preocupações e sintomas depressivos com influência mutua homogênea.…”
Section: 1) Verificar Se Há Um Padrão De Rotas Homogêneounclassified
“…Como os dados deste estudo provêm de um ECR, ao invés de um estudo naturalístico utilizando coortes (e.g.,Snyder et al, 2009, Kristman-Valente et al, 2016, a randomização dos participantes permitiu visualizar um retrato das potenciais interferências dos grupos TCBA e TAND nos padrões de rotas. A psicoterapia TCBA, como descrita no método, é diretiva, composta por um conjunto de atividades previamente selecionadas e com enfoque nos sintomas do diagnóstico de TAG.…”
unclassified